Precious metal slurry for coating type ceramic surface sintering as well as preparation method and application of precious metal slurry

By using a combination of organic resin and glass powder in ceramic surface coating slurry, combined with vacuum homogenization treatment and glass powder with different softening temperatures, the dispersion and adhesion of precious metal pastes are solved, and high-end ceramic products are realized The density and adhesion of the product are suitable for the preparation of high-end gold/silver porcelain products.

CN119252526APending Publication Date: 2025-01-03CHANGCHUN GOLD RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411238937.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The dispersion of precious metal paste on the surface of existing ceramic ware is not ideal, and the adhesion and density control is difficult, resulting in insufficient uniformity and adhesion of metal layer after sintering, which is challenging for the preparation of high-end products.

Method used

Use organic resin and organic solvent to mix, add glass powder and precious metal powder at the control temperature, improve dispersion through vacuum homogenization treatment, and use glass powder at different starting softening temperatures to soften step by step to enhance the adhesion between metal and ceramic surfaces and compactness.

Benefits of technology

It achieves the uniformity and adhesion of the slurry, and has good density of the metal layer after calcination. It is suitable for the preparation of high-end gold/silver porcelain products, and overcomes the problems of prone to cracking, falling off and poor density of traditional slurries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252526A_ABST
    Figure CN119252526A_ABST
Patent Text Reader

Abstract

The invention provides a precious metal slurry for coating type ceramic surface sintering and a preparation method and application thereof, and relates to the technical field of ceramic vessel surface and gold / silver combination. The precious metal paste comprises the following components in percentage by mass: 65-85% of precious metal powder, 1.5-5% of organic resin, 10-30% of an organic solvent, 0.5-3% of mixed glass powder and 0.2-2% of a diluent. The preparation method comprises the following steps: heating and stirring the organic resin and the organic solvent until the organic resin and the organic solvent are fully dissolved to obtain the organic binder; the temperature of the organic binder is controlled to be 40-60 DEG C, the mixed glass powder is added and homogenized evenly, then the precious metal powder is added and homogenized evenly, rolling is conducted through a three-roller machine, a diluent is supplemented, homogenizing is conducted evenly, and the precious metal slurry is obtained. Through regulation and control of slurry components and control of key steps for preparing the gold / silver slurry, the obtained precious metal slurry is uniform in component, is smeared on the ceramic surface, is good in leveling property, is uniform in film thickness after being dried, is good in compactness of a roasted precious metal layer, is strong in binding force with ceramic, and is suitable for preparation of high-end gold / silver ceramic products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of combining a ceramic vessel surface with gold or silver, and in particular to a precious metal slurry for smearing ceramic surface sintering, and a preparation method and application thereof. Background Art

[0002] The gold / silver porcelain products made by sintering precious metal slurry with ceramics are noble and beautiful, and are deeply loved by consumers. There are currently two main methods for applying slurry to the surface of ceramic utensils: one is spraying and the other is coating. The slurry used in the spraying method has a low precious metal content and high production efficiency. It is generally used to produce medium and low-end silver porcelain products. The spraying process is prone to slurry loss. In addition, gold slurry is not suitable for spraying, and silver slurry with a relatively high silver content is not suitable for spraying due to its high viscosity. Therefore, gold slurry and silver slurry with a relatively high silver content are generally coated.

[0003] Compared with electronic slurries, precious metals used on the surface of ceramic appliances need to be applied over a large area, so the leveling properties of the slurry are very high. In addition, the slurry type has relatively high requirements for the adhesion between the slurry and the ceramic surface throughout the entire process, so the composition and preparation steps of the slurry need to be controlled to obtain a slurry with good leveling and strong adhesion, a good density of the metal layer after firing, and a smooth and bright surface after polishing.

[0004] In order to meet the leveling and film-forming properties of the slurry, resins with different properties are generally selected; in order to avoid cracking and bubbling of the slurry during the drying process and to achieve a good resin dissolution effect, a variety of solvents are usually selected; in order to increase the adhesion between the slurry and the ceramic surface, chemical bonds are generally introduced through organic matter.

[0005] The patent with publication number CN 111863312A discloses a spray-coated silver paste for 5G ceramic dielectric filter and a preparation method thereof. The silver paste comprises the following components by weight: 8-15 parts of organic binder, 68-82 parts of silver powder, 1.5-3.5 parts of solder, 0.5-2.0 parts of anti-settling agent, and 12-15 parts of volatile agent. The silver paste is prepared by the following method: (1) preparation of organic binder; (2) preparation of solder; (3) preparation of silver paste: silver powder, organic binder, solder, anti-settling agent and volatile agent are uniformly mixed according to mass percentage and mass part, rolled, dispersed, and viscosity adjusted to obtain a spray-coated silver paste for 5G ceramic dielectric filter. This patent uses a combination of multiple resins and multiple solvents. The hydroxyl group of hydroxyethyl cellulose increases hydrogen bonds and improves the adhesion between the slurry and the ceramic surface. However, in the process of preparing the slurry, the organic binder, inorganic binder, silver powder and other components are mixed at the same time, which is not conducive to the dispersion of the silver powder. The silver powder is easily wrapped to form agglomerates. Improper operation during rolling can easily cause it to be pressed into sheets. The problem of adhesion and density between the metal and ceramic surface during the slurry sintering process is not considered.

[0006] The patent with publication number CN 111312426A discloses a highly efficient 5G ceramic dielectric filter conductive silver paste and its preparation method. The formula is mainly composed of a preset mass percentage of conductive filler, inorganic binder, organic binder, solvent, inorganic oxide additive, dispersant and thixotropic agent, the conductive filler is spherical silver powder; the inorganic binder is glass powder; the organic binder is one or more combinations of ethyl cellulose, rosin, and acrylic resin; the solvent is aliphatic hydrocarbons, aliphatic hydrocarbon derivatives, derivatives of alcohols containing more than 8 carbon atoms, and acetate derivatives; the inorganic oxide additive is one or more combinations of zinc oxide, bismuth oxide, aluminum oxide, yttrium oxide, and magnesium oxide; the dispersant is one or two of triamine citric acid and polymethacrylic acid amine; the thixotropic agent is polyamide wax or hydrogenated castor oil. Although the patent prepares silver paste, glass paste, oxide paste and other components by stirring and grinding in steps, which improves the dispersion and rheology of the powder particles, the slurry components and operation process are too complicated, which is not conducive to the preparation of large quantities of slurry.

[0007] It can be seen that the dispersion of the slurry in the prior art is not ideal, the adhesion between the slurry and the ceramic surface is not controlled finely enough during the slurry drying and sintering process, and the glass powder in the sintering process affects the density of the metal layer. Summary of the invention

[0008] In view of the defects of the above-mentioned prior art, the purpose of the present invention is to provide a precious metal slurry for smearing ceramic surface sintering and its preparation method and application. The preparation method first mixes an organic resin with an organic solvent to obtain an organic binder, and controls the organic binder to be kept at 40°C to 50°C, then mixes the mixed glass powder and precious metal powder in steps, and adopts a vacuum homogenization method to reduce the generation of glass powder and silver powder agglomerates, improve the uniformity of the slurry, and improve the dispersibility of powder particles; the type and amount of organic resin and organic solvent are limited, so that the prepared slurry has good leveling properties; during drying, the diluent and solvent evaporate in steps, the film thickness is uniform, the film is not easy to crack or fall off, and the slurry has strong adhesion to the ceramic surface; glass powder A and glass powder B with different initial softening temperatures are used, and during the roasting process, glass powder A and glass powder B soften in steps, which enhances the adhesion between the metal and the ceramic surface and improves the density of the metal layer.

[0009] To achieve the above-mentioned purpose, the present invention provides a precious metal slurry for sintering the surface of a smearable ceramic. Calculated by mass fraction, the precious metal slurry for smearable ceramic surface sintering comprises the following components: 65% to 85% precious metal powder, 1.5% to 5% organic resin, 10% to 30% organic solvent, 0.5% to 3% mixed glass powder, and 0.2% to 2% diluent; the mixed glass powder is composed of glass powder A and glass powder B, and the initial softening temperature of the glass powder A is lower than the initial softening temperature of the glass powder B.

[0010] Furthermore, the initial softening temperature of the glass powder A is 400-490° C., the initial softening temperature of the glass powder B is 500-600° C., and the mass ratio of the glass powder A to the glass powder B is 1:1-3.

[0011] Furthermore, the initial softening temperature of the glass powder A is higher than the decomposition and volatilization temperature of the organic resin.

[0012] Furthermore, the organic resin is a mixture of hydroxyethyl cellulose and a second resin; the second resin is one or both of acrylic resin and polyvinyl butyral; the mass ratio of the hydroxyethyl cellulose to the second resin is 1 to 5:1.

[0013] Furthermore, the organic solvent is a mixture of a first solvent and a second solvent; the first solvent is one or both of alcohol ester dodecanedioate and diethylene glycol butyl ether acetate; the second solvent is one or both of dimethyl adipate and terpineol; in the organic solvent, the mass fraction of the first solvent is 40% to 65%.

[0014] Furthermore, the precious metal powder is one of gold and silver; the precious metal powder is spherical powder with a particle size of 2 to 5 μm.

[0015] Furthermore, the diluent is camphor oil or isoamyl acetate.

[0016] To achieve the above object, the present invention also provides a method for preparing the aforementioned precious metal slurry for sintering the surface of the smearable ceramic, comprising the following steps:

[0017] S1, heating and stirring an organic resin and an organic solvent until they are fully dissolved to obtain an organic binder;

[0018] S2, keeping the organic binder at 40°C to 50°C, adding the mixed glass powder to the organic binder, homogenizing and stirring for 3 to 12 minutes, and vacuumizing and homogenizing and stirring for 3 to 6 minutes to obtain a mixed binder;

[0019] The mixed glass powder is composed of glass powder A and glass powder B, the initial softening temperature of the glass powder A is 400-490° C., the initial softening temperature of the glass powder B is 500-600° C., and the mass ratio of the glass powder A to the glass powder B is 1:1-3;

[0020] S3, keeping the mixed binder at 40°C to 50°C, adding precious metal powder to the mixed binder, homogenizing and stirring for 3 to 12 minutes, and vacuumizing and homogenizing and stirring for 3 to 6 minutes to obtain an initial slurry;

[0021] S4, the initial slurry is rolled 5 to 8 times by a three-roll mill, and then a diluent is added in proportion and homogenized to obtain a precious metal slurry.

[0022] Furthermore, in step S2, the vacuum homogenization process refers to: rotating and homogenizing the mixture of the mixed glass powder and the organic binder, and vacuuming the negative pressure gradually to -100 KPa. 。

[0023] The precious metal slurry used for sintering the surface of the aforementioned smearable ceramic has uniform composition and good leveling properties when applied to the ceramic surface; after drying, the film thickness is uniform and the film is not prone to cracking or falling off; after firing, the precious metal layer has good density and strong bonding with the ceramic; after polishing, the precious metal layer is smooth and bright with a metallic luster. The slurry has high market value and is particularly suitable for the preparation of high-end gold / silver porcelain products.

[0024] The beneficial effects of the present invention are:

[0025] 1. The method for preparing precious metal slurry for sintering the surface of smearable ceramics provided by the present invention adopts hydroxyethyl cellulose mixed with at least one of acrylic resin and polyvinyl butyral as the organic resin. Hydroxyethyl cellulose has good moldability and can reduce the sedimentation of precious metal powders. Moreover, the hydroxyl groups therein can form more hydrogen bonds with the ceramic surface to enhance the adhesion between the dry film and the ceramic surface. The acrylic resin and polyvinyl butyral used have good fluidity and can improve the leveling of the slurry. The present invention controls the mass ratio of hydroxyethyl cellulose to other resins to 1 to 5:1, so that the moldability, ceramic surface adhesion and leveling of the prepared slurry are better, which better meets the requirements of smearable slurry.

[0026] 2. The present invention selects two glass powders A and B with different initial softening temperatures to form a mixed glass powder, wherein the initial softening temperature of the glass powder A is lower than that of the glass powder B, and the initial softening temperature of the glass powder A is higher than the decomposition and volatilization temperature of the organic resin. Thus, during the slurry sintering process, the glass powder etches the ceramic surface on the one hand, acting as a binder, and on the other hand, the organic matter decomposes and disappears, and the melting of the glass powder drives the silver powder to rearrange and form an interconnected network, acting as a skeleton.

[0027] If the softening temperature of the glass powder is too low, the resin may not be completely decomposed and the glass powder may begin to soften, resulting in resin residue; if the softening temperature of the glass powder is too high, the resin may decompose and volatilize, and the glass powder may not have enough time to level and fill the gaps between the precious metal powders. Therefore, the present invention uses two glass powders with initial softening temperatures to ensure that the glass powder softens and flows in steps, preventing the concentrated softening of the glass powder during the sintering process from driving the metal powder to slide downward, thereby enhancing the adhesion of the slurry during the sintering process, improving the uniformity of the metal layer after sintering, and avoiding the problem of the glass powder beginning to soften when the resin is not completely decomposed. In addition, the process of softening and leveling the glass powder to fill the gaps between the precious metal powders will affect the compactness of the precious metal layer. In the present invention, the two glass powders are softened in steps, and the process is gentle, which is conducive to improving the compactness of the precious metal layer.

[0028] 3. The present invention adopts a variety of organic solvents. On the one hand, the dissolution effect of hydroxyethyl cellulose and other resins is good under the synergistic effect of polar solvents and non-polar solvents. Diethylene glycol butyl ether acetate and alcohol ester twelve have strong polarity and good solubility in hydroxyethyl cellulose and acrylic resin, while polyvinyl butyral itself has good solubility. Therefore, diethylene glycol butyl ether acetate and alcohol ester twelve can open the self-entanglement between polar functional groups on the molecular chain, so that the resin molecular chain can be stretched as much as possible, thereby reducing the carrier viscosity and making the slurry film-forming property good. On the other hand, the volatilization rates of these solvents are all different. During the drying and sintering process of the slurry, the solvent is gradually released, so that the obtained film thickness is uniform, and the metal layer is flat after sintering, which overcomes the shortcomings of pores and peeling on the surface of traditional slurry.

[0029] 4. The present invention controls the key steps in the slurry preparation process, adds glass powder and precious metal powder to the organic binder in a step-by-step and orderly manner, and maintains the dissolved organic binder at 40-50°C to improve its fluidity, ensure the full mixing of the glass powder and precious metal powder with the organic binder, and greatly improve the dispersion of the powder. The vacuum negative pressure homogenization can break up the agglomeration of the glass powder or precious metal powder. If the glass powder or precious metal powder agglomerates and is then wrapped by the organic binder, it will agglomerate into lumps during the homogenization process, which is not conducive to the dispersion of the glass powder or precious metal powder. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a surface SEM image of the silver layer prepared in Example 1.

[0031] Figure 2 This is a surface electron microscope image of the silver layer prepared in Example 1.

[0032] Figure 3 This is a surface electron microscope image of the silver layer prepared in Comparative Example 1.

[0033] Figure 4 This is a surface electron microscope image of the silver layer prepared in Comparative Example 2.

[0034] Figure 5 This is a surface SEM image of the silver layer prepared in Example 2.

[0035] Figure 6 This is the surface SEM image of the silver layer prepared in Comparative Example 3.

[0036] Figure 7 This is a surface electron microscope image of the silver layer prepared in Comparative Example 4.

[0037] Figure 8 This is the surface SEM image of the silver layer prepared in Example 7.

[0038] Fig. 9 This is a surface electron microscope image of the silver layer prepared in Example 7.

[0039] Fig.10 This is the surface SEM image of the gold layer prepared in Example 8.

[0040] Fig.11 This is a surface electron microscope image of the gold layer prepared in Example 8. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0042] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.

[0043] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0044] The present invention provides a precious metal slurry for sintering the surface of a smearable ceramic. The precious metal slurry for smearable ceramic surface sintering comprises the following components by mass fraction: 65-85% of precious metal powder, 1.5-5% of organic resin, 10-30% of organic solvent, 0.5%-3% of mixed glass powder, and 0.2%-2% of diluent; the mixed glass powder consists of glass powder A and glass powder B, and the initial softening temperature of glass powder A is lower than the initial softening temperature of glass powder B.

[0045] The initial softening temperature of glass powder A is 400-490°C, the initial softening temperature of glass powder B is 500-600°C, and the mass ratio of glass powder A to glass powder B is 1:1-3. The initial softening temperature of glass powder A is higher than the decomposition and volatilization temperature of the organic resin.

[0046] In this way, it is ensured that after the organic matter is completely decomposed, the glass powder A and the glass powder B begin to soften and flow step by step, preventing the glass powder from softening in the sintering process and driving the metal powder to slide downward, thereby enhancing the adhesion of the slurry during the sintering process, improving the uniformity of the metal layer after sintering, and avoiding the problem of the glass powder beginning to soften when the resin is not completely decomposed. In addition, the process of glass powder softening and leveling to fill the gaps between the precious metal powders will affect the compactness of the precious metal layer. In the present invention, the two glass powders are softened step by step, and the process is gentle, which is conducive to improving the compactness of the precious metal layer.

[0047] The organic resin is mixed with hydroxyethyl cellulose and a second resin; the second resin is one or two of acrylic resin and polyvinyl butyral; the mass ratio of hydroxyethyl cellulose to the second resin is 1-5:1.

[0048] The organic solvent is a mixture of a first solvent and a second solvent; the first solvent is one or both of alcohol ester dodecanedioate and diethylene glycol butyl ether acetate; the second solvent is one or both of dimethyl adipate and terpineol; in the organic solvent, the mass fraction of the first solvent is 40% to 65%.

[0049] A variety of organic solvents are used. On the one hand, they have a good dissolution effect on hydroxyethyl cellulose and other resins under synergistic effect. On the other hand, the volatilization rates of these solvents are different. During the drying and sintering process of the slurry, the solvent is gradually released, so that the prepared film thickness is uniform and the metal layer is flat after sintering, overcoming the shortcomings of pores and peeling on the surface of traditional slurry.

[0050] The precious metal powder is one of gold and silver; the precious metal powder is spherical powder with a particle size of 2 to 5 μm. The diluent is camphor oil or isoamyl acetate.

[0051] The present invention provides a method for preparing a precious metal slurry for sintering a smearable ceramic surface, comprising the following steps:

[0052] S1, heating and stirring an organic resin and an organic solvent until they are fully dissolved to obtain an organic binder;

[0053] S2, keeping the organic binder at 40°C to 50°C, adding the mixed glass powder to the organic binder, homogenizing and stirring for 3 to 12 minutes, and vacuumizing and homogenizing and stirring for 3 to 6 minutes to obtain a mixed binder;

[0054] The mixed glass powder consists of glass powder A and glass powder B, the initial softening temperature of glass powder A is 400-490° C., the initial softening temperature of glass powder B is 500-600° C., and the mass ratio of glass powder A to glass powder B is 1:1-3;

[0055] S3, keeping the mixed binder at 40°C to 50°C, adding precious metal powder to the mixed binder, homogenizing and stirring for 3 to 12 minutes, and vacuumizing and homogenizing and stirring for 3 to 6 minutes to obtain an initial slurry;

[0056] S4, the initial slurry is rolled 5 to 8 times by a three-roll mill, and then a diluent is added in proportion and homogenized to obtain a precious metal slurry.

[0057] Among them, in step S2, vacuum homogenization treatment refers to: rotating and homogenizing the mixture of mixed glass powder and organic binder, and vacuuming the negative pressure gradually to -100KPa 。

[0058] The agglomeration of glass powder or precious metal powder can be broken up. If the glass powder or precious metal powder is agglomerated and then wrapped by an organic binder, it will agglomerate into lumps during the homogenization process, which is not conducive to the dispersion of the glass powder or precious metal powder.

[0059] The precious metal slurry used for sintering the surface of smearable ceramics has uniform composition and good leveling properties when applied to the ceramic surface. After drying, the film thickness is uniform and the film is not prone to cracking or falling off. After roasting, the precious metal layer has good density and strong bonding with the ceramic. After polishing, the precious metal layer is smooth and bright with a metallic luster. The slurry has high market value and is particularly suitable for the preparation of high-end gold / silver ceramic products.

[0060] The following is a description of the method for preparing the precious metal slurry for sintering the surface of smearable ceramics provided by the present invention in conjunction with specific examples. Unless otherwise specified, the raw materials and reagents in the examples of the present application are purchased through commercial channels.

[0061] Example 1

[0062] This embodiment provides a precious metal slurry for sintering the surface of a smearable ceramic, and its raw material composition is shown in Table 1:

[0063] Table 1 Raw material composition of silver paste provided in Example 1

[0064]

[0065]

[0066] The particle size of the silver powder is in the range of 2 to 5 μm, the initial softening temperature of the glass powder A is 450°C, and the initial softening temperature of the glass powder B is 550°C.

[0067] This embodiment also provides a method for preparing the precious metal slurry for sintering the above-mentioned smearable ceramic surface, comprising the following steps:

[0068] S1, first heat and stir 0.7g hydroxyethyl cellulose, 0.2g acrylic resin, 4.5g diethylene glycol butyl ether acetate, 1.4g dimethyl adipate, and 1.5g pinene alcohol until fully dissolved to obtain an organic binder;

[0069] S2, keeping the organic binder at 40°C to 50°C, adding 0.2g of glass powder A and 0.2g of glass powder B to the organic binder, stirring homogenously for 3min, and vacuumizing and stirring homogenously for 6min to obtain a mixed binder;

[0070] S3, keeping the mixed binder at 40°C to 50°C, adding 21g of spherical silver powder with a particle size of 2 to 5 μm to the mixed binder, homogenizing and stirring for 3 minutes, and vacuumizing and homogenizing and stirring for 6 minutes to obtain an initial slurry;

[0071] S4, the initial slurry is rolled 8 times by a three-roll mill, 0.1 g of camphor oil is added, and the mixture is homogenized to obtain a silver paste.

[0072] The silver paste prepared in this embodiment is applied to the ceramic surface. The silver paste has good leveling property. After the application, it is placed in a blast drying oven and dried at 60°C for 4 hours. The diluent and the solvent are evaporated step by step. After the film is dried, no cracking, shedding or bubbles are found. It is placed in a roasting furnace and gradually heated to 800°C. The heating time is controlled to be 3 hours. After reaching 800°C, it is kept warm for 10 minutes. The roasting furnace is closed and cooled to room temperature. After polishing, the silver layer is dense, the surface is smooth and bright, and the SEM picture of the silver layer is as follows Figure 1 As shown in FIG. 2, it can be seen that under a scanning electron microscope at 2300 times, the silver layer is flat and has good density.

[0073] Its electron microscope image is as follows Figure 2 As shown, it can be seen that the surface of the silver layer is smooth and flat.

[0074] Comparative Example 1

[0075] Comparative Example 1 provides a method for preparing a precious metal slurry for sintering a smearable ceramic surface, which is different from Example 1 mainly in that the initial softening temperature of glass powder A and glass powder B is the same, both of which are 450°C.

[0076] Experiments show that when the slurry is applied to ceramic utensils, it begins to soften at 450°C, driving the silver powder to move and align. Due to gravity, the silver powder flows downward, and the adhesion is insufficient, resulting in poor uniformity of the metal layer after sintering. The electron microscope image of the silver layer is shown below. Figure 3 shown.

[0077] Comparative Example 2

[0078] Comparative Example 2 provides a method for preparing a precious metal slurry for sintering a smearable ceramic surface. The difference from Example 1 is that the initial softening temperature of the glass powder A is 350°C, which is lower than the decomposition temperature of the organic resin.

[0079] Experiments show that during firing, the glass powder A has melted because the resin has not been completely decomposed and volatilized, resulting in incomplete decomposition and volatilization of the resin. A part of it remains in the metal layer, resulting in a darker color of the metal layer, and a weaker adhesion between the metal layer and the ceramic. The bond is not strong enough, and the silver layer is easy to fall off when polished. The electron microscope image of the silver layer is as follows Figure 4 shown.

[0080] Example 2 and Comparative Examples 3-4

[0081] Example 2 and Comparative Examples 3-4 provide a method for preparing a precious metal slurry for sintering a smear-type ceramic surface. The difference from Example 1 mainly lies in: changing the mass ratio of glass powder A to glass powder B; as shown in the table below, other operations are generally the same as Example 1 and will not be repeated here.

[0082]

[0083] The experiment shows that the metal layers after calcination in Example 1 and Example 2 are uniform, have strong adhesion and good compactness. The surface SEM image of the silver layer prepared in Example 2 is as follows: Figure 5 As shown, it can be seen that when the SEM is magnified 105 times, the overall density of the silver layer is good.

[0084] In Comparative Example 3, since the content of glass powder B is too high and the content of glass powder A is low, the organic resin decomposes and volatilizes, but the overall melting temperature of the glass powder is too high to fill the gaps caused by the decomposition and volatilization of the resin, so the density of the metal layer is poor.

[0085] At the same magnification (105 times), the density of the silver layer prepared in Comparative Example 3 is as follows: Figure 6 As shown, its density is worse than that of Example 2.

[0086] In Comparative Example 4, the content of glass powder A is too high, and the glass powder begins to soften at 450° C., driving the metal powder to flow, resulting in poor adhesion and poor uniformity of the metal layer.

[0087] The surface electron microscope image of the silver layer prepared in Comparative Example 4 is as follows Figure 7 As shown, it can be seen that the adhesion of the silver layer is poor, resulting in poor uniformity of the silver layer.

[0088] Examples 3-4 and Comparative Examples 5-6

[0089] Examples 3-4 and Comparative Examples 5-6 provide a method for preparing a precious metal slurry for sintering a coating-type ceramic surface, which differs from Example 1 mainly in that the composition of the organic resin and the mass ratio of hydroxyethyl cellulose to other resins are changed; as shown in the table below, other operations are substantially the same as in Example 1 and will not be repeated here.

[0090]

[0091]

[0092] The experiment found that the slurries obtained in Examples 1 to 4 had good film-forming properties, moderate slurry viscosity, and good leveling properties. After sintering, the surface of the silver layer was flat and smooth.

[0093] The reason is that the ratio of hydroxyethyl cellulose to other resins is moderate. Hydroxyethyl cellulose mainly promotes the film-forming property of the slurry and ensures good suspension of the powder in the slurry, while other resins have low viscosity and can improve the leveling property of the slurry. The hydroxyl groups in hydroxyethyl cellulose can form more hydrogen bonds with the ceramic surface, enhancing the adhesion between the film and the ceramic surface during the drying process.

[0094] However, in Comparative Example 5, the amount of hydroxyethyl cellulose used is too large, the viscosity of the slurry is relatively large, the leveling property is relatively poor, and it is not suitable for coating.

[0095] In Comparative Example 6, hydroxyethyl cellulose was not used, and as a result, the viscosity of the slurry was too low and unsuitable for coating.

[0096] Examples 5-6 and Comparative Example 7

[0097] The main difference between Examples 5-6 and Comparative Example 7 and Example 1 is that the composition of the organic solvent and the sum of the mass fractions of diethylene glycol butyl ether acetate and alcohol ester twelve in the organic solvent are changed; as shown in the following table, other operations are generally the same as in Example 1 and will not be repeated here.

[0098]

[0099] As shown in the table above, the main difference between Example 5 and Example 1 is that terpineol is replaced with terpineol dodecahydrate and the dosage is adjusted. Other operations are substantially the same as those in Example 1 and will not be described in detail here.

[0100] As shown in the table above, the main difference between Comparative Example 7 and Example 1 is that diethylene glycol butyl ether acetate is replaced with alcohol ester dodecahydrate, and the content of alcohol ester dodecahydrate is less than 40%. Other operations are generally the same as those in Example 1 and will not be repeated here.

[0101] Experiments show that in Examples 1 to 6, since the three solvents are matched with each other, the solvent evaporation temperatures are different, and the ratio of polar and non-polar solvents is reasonably matched, the film-forming property and leveling property of the slurry are relatively good. During the drying process, the slurry does not bubble or fall off, and the silver layer has good flatness after sintering.

[0102] However, in Comparative Example 7, the dosage of diethylene glycol butyl ether acetate and alcohol ester twelve was reduced, the slurry forming property of the slurry became worse, the viscosity increased, and the leveling property was poor.

[0103] The reason is that diethylene glycol butyl ether acetate and alcohol ester have strong polarity. After reducing the dosage, the self-entanglement between the polar functional groups on the resin molecular chain cannot be completely opened. Therefore, the viscosity of the organic binder is high and the leveling property of the silver paste is poor.

[0104] Example 7

[0105] Table 2 Raw material composition of silver paste provided in Example 7

[0106] Raw material name Mass(g) Mass fraction (%) Spherical silver powder 24 80 Solvent: Diethylene glycol butyl ether acetate 2 6.67 Solvent: Dimethyl adipate 0.8 2.67 Solvent: terpineol 1.0 3.33 Resin: Hydroxyethyl Cellulose 0.6 2 Resin: Acrylic resin 0.3 1 Resin: Polyvinyl butyral 0.2 0.67 Glass powder A 0.3 1 Glass powder B 0.4 1.33 Diluent: Isoamyl acetate 0.4 1.33 total 30 100

[0107] In Example 7, the content of silver powder is increased, and the silver paste prepared in this example is applied to the ceramic surface. The silver paste has good leveling properties. After application, it is placed in a blast drying oven and dried at 60°C for 4 hours. The diluent and solvent evaporate step by step. After the film is dried, no cracking, falling off or bubbles are found. It is placed in a roasting furnace and gradually heated to 800°C. The heating time is controlled to be 3 hours. After reaching 800°C, it is kept warm for 10 minutes. The roasting furnace is turned off and cooled to room temperature. After polishing, the silver layer is dense and the surface is smooth and bright.

[0108] Experiments show that the silver layer obtained in Example 7 has good compactness, and the SEM image of the prepared silver layer is as follows: Figure 8 The electron microscope image is shown in Fig. 9 As shown, it can be seen that the surface of the silver layer is smooth and flat.

[0109] Example 8

[0110] The main difference between Example 8 and Example 1 is that the 2-5 μm spherical silver powder is replaced with 2-5 μm spherical gold powder. Other operations are substantially the same as those in Example 1 and will not be described again.

[0111] The gold paste prepared in this embodiment is applied to the ceramic surface. The gold paste has good leveling properties. After application, it is placed in a blast drying oven and dried at 60°C for 4 hours. The diluent and solvent evaporate step by step. After the film is dried, no cracking, falling off or bubbles are found. It is placed in a roasting furnace and gradually heated to 800°C. The heating time is controlled to be 3 hours. After reaching 800°C, it is kept warm for 10 minutes. The roasting furnace is closed and cooled to room temperature. After polishing, the gold layer is dense and the surface is smooth and bright.

[0112] The SEM image of the gold layer is as follows: Fig.10 As shown, it can be seen that the gold layer has good density, just like the silver layer.

[0113] The surface electron microscope image of the gold layer is as follows Fig.11 As shown, it can be seen that the surface of the gold layer is flat and smooth.

[0114] It should be noted that in other embodiments of the present invention, the mass fraction of each component in the precious metal slurry can also be adjusted on the basis of Example 1, so that the mass fraction of each component in the precious metal slurry meets the standards of 65% to 85% precious metal powder, 1.5% to 5% organic resin, 10% to 30% organic solvent, 0.5% to 3% mixed glass powder, and 0.2% to 2% diluent.

[0115] In summary, the method for preparing precious metal slurry for sintering the surface of smearable ceramics provided by the present invention, through the regulation of the slurry composition and the control of the key steps of preparing silver paste, the precious metal slurry has uniform composition, and when applied to the ceramic surface, it has good leveling property. After drying, the film thickness is uniform, and the film is not prone to cracking or falling off. After roasting, the precious metal layer has good density and strong bonding with the ceramic. After polishing, the precious metal layer is smooth and bright with metallic luster. The slurry has high market value and is particularly suitable for the preparation of high-end gold / silver porcelain products.

[0116] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.

Claims

1. A precious metal slurry for sintering a smearable ceramic surface, characterized in that: Measured by mass fraction, the precious metal slurry used for sintering the smearable ceramic surface comprises the following components: 65-85% precious metal powder, 1.5-5% organic resin, 10-30% organic solvent, 0.5%-3% mixed glass powder, and 0.2%-2% diluent; the mixed glass powder is composed of glass powder A and glass powder B, and the initial softening temperature of the glass powder A is lower than the initial softening temperature of the glass powder B.

2. The precious metal slurry for sintering the surface of smearable ceramics according to claim 1, characterized in that: The initial softening temperature of the glass powder A is 400-490° C., the initial softening temperature of the glass powder B is 500-600° C., and the mass ratio of the glass powder A to the glass powder B is 1:1-3.

3. The precious metal slurry for sintering the surface of smearable ceramics according to claim 1, characterized in that: The initial softening temperature of the glass powder A is higher than the decomposition and volatilization temperature of the organic resin.

4. The precious metal slurry for sintering the surface of smearable ceramics according to claim 1, characterized in that: The organic resin is formed by mixing hydroxyethyl cellulose and a second resin; the second resin is one or both of acrylic resin and polyvinyl butyral; the mass ratio of the hydroxyethyl cellulose to the second resin is 1 to 5:

1.

5. The precious metal slurry for sintering the surface of smearable ceramics according to claim 1, characterized in that: The organic solvent is a mixture of a first solvent and a second solvent; the first solvent is one or both of alcohol ester dodecanedioate and diethylene glycol butyl ether acetate; the second solvent is one or both of dimethyl adipate and terpineol; in the organic solvent, the mass fraction of the first solvent is 40% to 65%.

6. The precious metal slurry for sintering the surface of smearable ceramics according to claim 1, characterized in that: The precious metal powder is one of gold and silver; the precious metal powder is spherical powder with a particle size of 2 to 5 μm.

7. The precious metal slurry for sintering the surface of smearable ceramics according to claim 1, characterized in that: The diluent is camphor oil or isoamyl acetate.

8. A method for preparing the precious metal slurry for sintering the surface of smearable ceramics as claimed in any one of claims 1 to 7, characterized in that: The steps include: S1, heating and stirring an organic resin and an organic solvent until they are fully dissolved to obtain an organic binder; S2, keeping the organic binder at 40°C to 50°C, adding the mixed glass powder to the organic binder, homogenizing and stirring for 3 to 12 minutes, and vacuumizing and homogenizing and stirring for 3 to 6 minutes to obtain a mixed binder; The mixed glass powder is composed of glass powder A and glass powder B, the initial softening temperature of the glass powder A is 400-490° C., the initial softening temperature of the glass powder B is 500-600° C., and the mass ratio of the glass powder A to the glass powder B is 1:1-3; S3, keeping the mixed binder at 40°C to 50°C, adding precious metal powder to the mixed binder, homogenizing and stirring for 3 to 12 minutes, and vacuumizing and homogenizing and stirring for 3 to 6 minutes to obtain an initial slurry; S4, the initial slurry is rolled 5 to 8 times by a three-roll mill, and then a diluent is added in proportion and homogenized to obtain a precious metal slurry.

9. The method for preparing the precious metal slurry for sintering the surface of smearable ceramics according to claim 8, characterized in that: In step S2, vacuum homogenization treatment refers to rotating and homogenizing the mixture of the mixed glass powder and the organic binder while vacuuming the negative pressure gradually to -100 KPa. 。 10. An application of the precious metal slurry for sintering the surface of smearable ceramics according to any one of claims 1 to 7, characterized in that: The precious metal slurry for sintering the surface of the smearable ceramic is used for preparing gold / silver ceramic products.